Pengaruh Deforestasi, Jumlah Industri, dan Tingkat Urbanisasi Terhadap Indeks Kualitas Lingkungan Hidup dalam Perspektif Ekonomi Islam (Studi Sumbagsel Tahun 2015-2024) - Safitri Fitri; Liya Ermawati; Is Susanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of deforestation, the number of industries, and the level of urbanization on the Environmental Quality Index (IKLH) in the provinces of South Sumatra Region (Jambi, South Sumatra, Bengkulu, Lampung, and the Bangka Belitung Islands) from an Islamic economic perspective. This research uses a quantitative method with secondary data in the form of panel data from 2015 to 2024. The sampling technique used was saturated sampling with 5 provinces as cross-sectional units over 10 years, resulting in 50 observation data points. The data were analyzed using panel data regression analysis. The model selection tests (Chow and Hausman tests) indicated that the Fixed Effect Model (FEM) is the most appropriate. The results partially show that the number of industries has a negative and significant effect, and the level of urbanization has a positive and significant effect on the IKLH. Meanwhile, deforestation has a negative but insignificant effect on the IKLH at a 95% confidence level. Simultaneously, deforestation, the number of industries, and the level of urbanization have a significant effect on the IKLH in the South Sumatra Region. In the perspective of Islamic economics, these findings emphasize the importance of the principles of balance (tawazun), preventing damage (dar'u al-mafasid), and moral supervision (hisbah) in managing natural resources for the creation of public welfare (maslahah).